2023
DOI: 10.3390/jcm12103490
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Percutaneous Tibial Nerve Stimulation (PTNS) as a Minimally Invasive, Non-Surgical, Non-Hormonal Treatment for Overactive Bladder Symptoms

Connor McPhail,
Robert Carey,
Sidharth Nambiar
et al.

Abstract: Background: Overactive bladder (OAB) syndrome affects 10–15% of women, severely impacting their quality of life. First-line treatments include behavioural and physical therapy, and second-line medical treatments include medications such as vaginal oestrogen, anticholinergic medications, and ß3-adrenergic agonists—with potential adverse side effects including dizziness, constipation, and delirium, particularly affecting elderly populations. Third-line treatments include more invasive measures, including intrade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Randomized controlled studies show that PTNS has a success rate that is significantly higher than placebo. Compared to control groups, PTNS significantly improved bladder control and reduced urinary urgency and frequency in systematic reviews and meta-analyses [27]. The findings affirm the positive efficacy of PTNS as a minimally invasive, non-surgical, and non-hormonal treatment for OAB.…”
Section: Ptns Efficacy For Detrusor Overactivity Treatment In Ms Pati...supporting
confidence: 58%
See 1 more Smart Citation
“…Randomized controlled studies show that PTNS has a success rate that is significantly higher than placebo. Compared to control groups, PTNS significantly improved bladder control and reduced urinary urgency and frequency in systematic reviews and meta-analyses [27]. The findings affirm the positive efficacy of PTNS as a minimally invasive, non-surgical, and non-hormonal treatment for OAB.…”
Section: Ptns Efficacy For Detrusor Overactivity Treatment In Ms Pati...supporting
confidence: 58%
“…The findings affirm the positive efficacy of PTNS as a minimally invasive, non-surgical, and non-hormonal treatment for OAB. Furthermore, it has been demonstrated that PTNS has a long-lasting impact: patients report symptom improvement for one to three months following the procedure [27].…”
Section: Ptns Efficacy For Detrusor Overactivity Treatment In Ms Pati...mentioning
confidence: 99%